Antimicrobial Effects of Tannic Acid Combined with Plasma-Activated Water and Their Application in Strawberry Preservation - Zhixiang Hu; Zhenyang Hu; Huan Zhang; Zhilong Yu; Yunfei Xie (Foods, 2025)
This study investigated the combined antibacterial effects of PAW with natural antimicrobial agents and further examined the impact of this technology on postharvest strawberry preservation. The optimal PAW preparation condition was determined at 50 min at 400 W, although PAW alone showed limited efficacy against Staphylococcus aureus and Escherichia coli. Among the five selected natural antimicrobial agents, the 1% tannic acid–PAW combined treatment demonstrated optimal bactericidal performance, achieving reductions of 3.62 log CFU/mL for S. aureus in 20 min and 5.13 log CFU/mL for E. coli in 8 min. The results revealed membrane damage in both S. aureus and E. coli, with leakage of intracellular proteins and nucleic acids, decreased membrane protein content, and cellular shrinkage and collapse observed morphologically. Increased MDA content indicated membrane lipid peroxidation, while elevated intracellular H2O2 and ROS levels resulted from oxidative stress induced by PAW’s reactive species. Tannic acid reduced SOD and CAT enzyme activities, impairing bacterial antioxidant capacity, and PAW further exacerbated the decline in SOD and CAT activities, intensifying oxidative stress and disrupting bacterial physiological balance. In strawberry preservation applications, the combined treatment reduced surface microbial loads, decreased mold incidence and weight loss, slowed the deterioration of color, firmness, and edible quality, and enhanced antioxidant capacity. The results suggest that the tannic acid–PAW combined treatment offers a promising strategy for enhancing microbial safety and extending the shelf life of strawberries.